Lymphocyte Rich Hodgkin's Lymphoma Presented with Warm Hemolytic Anemia: A Case Report and Literature Review - Hurtado-Cordovi, Jorge M.; Verma, Vaibhav; Gotlieb, Vladimir; Frieri, Marianne (Case Reports in Hematology, 2011)
Hodgkin's lymphoma accounts for ten percent of all lymphomas. In the United States, there are about 8000 new cases every year. This paper describes a case of lymphocyte-rich Hodgkin's lymphoma (LRHL) manifested by autoimmune hemolytic anemia (AIHA). A 27-year-old Israeli male presented with dizziness associated with one month of low-grade fevers and night sweats; he also complained of persistent cough, pruritus, and ten-pound weight lost during this time. The CBC revealed hemoglobin of 5.9 gm/dL, and direct Coomb's test detected multiple nonspecific antibodies consistent with the diagnosis of AIHA. Chest, abdomen, and pelvic CT scan showed mediastinal lymphadenopathy and splenomegaly. Lymph node biopsy revealed classic LRHL. AIHA resolved after completion of the first cycle of chemotherapy with adriamycin, bleomycin, vinblastine, and dacarbazine (ABVD); after six cycles, he went into complete remission. Although infrequent, AIHA can be responsible for the presenting symptoms of HL.